2023
DOI: 10.1088/1741-2552/acb085
|View full text |Cite
|
Sign up to set email alerts
|

Outer retinal degeneration in a non-human primate model using temporary intravitreal tamponade with N-methyl-N-nitrosourea in cynomolgus monkeys

Abstract: The main objective of this study was to induce and evaluate drug-dose-dependent outer retinal degeneration in cynomolgus monkeys by application of N-methyl-N-nitrosourea (MNU). Intravitreal temporary tamponade induced outer retinal degeneration with N-methyl-N-nitrosourea (MNU) solutions (2–3 mg/mL) after vitrectomy in five cynomolgus monkeys. Optical coherence tomography (OCT), fundus autofluorescence (FAF), full-field electroretinography (ffERG), and visual evoked potentials (VEP) were performed at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…While this study successfully demonstrated the efficacy of burst stimulation in normal and degenerate mouse models, its feasibility for human clinical studies necessitates validation in a non-human primate model that closely resembles a human retinal system. Our previous work established an RD monkey model [ 39 ], highlighting the drawbacks of single high-amplitude pulse stimulation on RGC response resolution [ 6 ]. Our upcoming research will assess the efficacy of burst stimulation to enhance spatial resolution in the RD monkey model, potentially enabling translation into human clinical studies based on insights from the non-human primate model.…”
Section: Discussionmentioning
confidence: 99%
“…While this study successfully demonstrated the efficacy of burst stimulation in normal and degenerate mouse models, its feasibility for human clinical studies necessitates validation in a non-human primate model that closely resembles a human retinal system. Our previous work established an RD monkey model [ 39 ], highlighting the drawbacks of single high-amplitude pulse stimulation on RGC response resolution [ 6 ]. Our upcoming research will assess the efficacy of burst stimulation to enhance spatial resolution in the RD monkey model, potentially enabling translation into human clinical studies based on insights from the non-human primate model.…”
Section: Discussionmentioning
confidence: 99%
“…In Vitro Subretinal Stimulation: Retinal patches were isolated from two 10-week-old wild-type mice (C57BL/6J strain) and two adult male cynomolgus monkeys (Macaca fascicularis) with outer retinal degeneration induced by N-methyl-N-nitrosourea [49] (Figure S7a,b, Supporting Information). The retinal patch was attached to the recording electrode array (60pMEA200/30iR-Ti, Multichannel Systems GmbH, Germany) with the ganglion cell layer facing down contacting recording electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…This study used adult male cynomolgus monkeys (Macaca fascicularis) with normal (n = 3) and outer RD induced by MNU (n = 3) [19]. The monkeys had a mean age of 53.6 ± 2.2 months and a mean body weight of 3.7 ± 0.4 kg.…”
Section: Animalsmentioning
confidence: 99%
“…The subjects were sacrificed approximately 14-21 weeks after MNU administration. The housing condition, how to euthanize, and the detailed methods of the operation for vitrectomy and injection of MNU were described in our previous study [19].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation